Optimization of Rice Planting Practices using Gripper Technology in Robot Application: Optimization of Rice Planting Practices using Gripper Technology in Robot Application - Siswoyo, Agus (Jurnal Teknologi, 2024)
The optimization of rice planting practices using advanced gripper technology in robotic systems represents a significant advancement in agricultural automation. Traditional rice planting methods, typically labor-intensive and prone to inconsistencies, can be enhanced through the integration of mechatronic systems, providing precise and efficient handling of rice seedlings. This study investigates the design, implementation, and optimization of a gripper system specifically tailored for rice planting, leveraging the context of competitive robotics to drive innovation. The gripper technology, a cornerstone of agricultural robotics, must achieve a delicate balance between precision and gentleness to handle fragile seedlings without causing damage. This involves the convergence of mechanical engineering, materials science, and advanced control systems to replicate the dexterity and sensitivity of human hands. The gripper system developed for this study incorporates cutting-edge sensors, including force, proximity, and visual sensors, which enable the adaptive handling of seedlings based on their size and condition. Machine learning algorithms further enhance the system's performance by allowing it to learn from previous planting cycles, improving efficiency and accuracy over time. Field tests and simulations were conducted to evaluate the gripper's effectiveness in various planting conditions. The results demonstrated a significant improvement in planting precision and seedling survival rates compared to traditional methods. Additionally, the system showed promise in reducing labor costs and increasing overall productivity. The broader implications of this technology extend beyond rice planting, with potential applications in various agricultural settings where precision and care are paramount. This research not only contributes to the field of precision agriculture but also sets the stage for future advancements in sustainable farming practices. The findings highlight the potential of robotic systems to revolutionize agricultural processes, making them more efficient, reliable, and scalable.